Book Review: Jean Dreze and Amartya Sen, An Uncertain Glory: India and Its Contradictions. (January 2016) - Jain, Ektaa
Jean Dreze and Amartya Sen, An Uncertain Glory: India and Its Contradictions, 2013, London: Penguin, pp. 433, ₹ 599, ISBN 978-0-141-97582-5.